2016
DOI: 10.1007/s00402-016-2474-0
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with the course of health-related quality of life after a hip fracture

Abstract: Both PCS and MCS HRQoL declined after a hip fracture and PCS did not recover to baseline values. Healthier patients may need extra care to prevent them from having a steep decline in postoperative PCS HRQoL and arthroplasty should be considered with low threshold.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
28
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 36 publications
6
28
0
2
Order By: Relevance
“…This is in accordance with studies of the same cohort of hip fracture patients as the current study. The studies focusing on of the level of mobility and health‐related quality of life showed that the most mobile patients were least likely to return to their prefracture mobility level and the healthier patients were less likely to return to their prefracture health‐related quality of life level . These healthier and more active patients have more to lose.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This is in accordance with studies of the same cohort of hip fracture patients as the current study. The studies focusing on of the level of mobility and health‐related quality of life showed that the most mobile patients were least likely to return to their prefracture mobility level and the healthier patients were less likely to return to their prefracture health‐related quality of life level . These healthier and more active patients have more to lose.…”
Section: Discussionsupporting
confidence: 89%
“…The studies focusing on of the level of mobility and health-related quality of life showed that the most mobile patients were least likely to return to their prefracture mobility level and the healthier patients were less likely to return to their prefracture health-related quality of life level. 23,24 These healthier and more active patients have more to lose. The type of anesthesia was no predictor in ADL decline between baseline and 3 months.…”
Section: Discussionmentioning
confidence: 99%
“…Our study population is mainly composed of women over the age of 80, not institutionalized, which is in line with other studies [16,[28][29][30][31][32][33]. The length of hospitalisation was 5.3 days (±1.2), considerably less than what was reported in the Úbeda study.…”
Section: Discussionsupporting
confidence: 84%
“…The work carried out by [36] showed variations of 0.78 before the fracture, 0.59 at 4 months and 0.51 at 17 months. The smaller difference between the pre-fracture value and successive values compared to our study can be explained by the increase in the quality of life as a result of the recovery and rehabilitation process [33]. Another possible explanation for higher scores over longer follow-up periods could be the "response to change," where patients become accustomed to their illness or experience changes in their expectations about their state of health [37].…”
Section: Discussionmentioning
confidence: 70%
“…Future investigations may deepen in this approach and in the quality of life rather than in-hospital mortality for evaluating outcome in elderly trauma patients[67,68]. Returning to their baseline quality of life is difficult in these patients, even in relatively minor trauma[69]. This expectative must be discussed with the patient (if possible) and relatives when we consider the treatment alternatives of elderly trauma patients.…”
Section: Postacute Care and Palliative Carementioning
confidence: 99%